Evaluation of malted barley with different degrees of fermentability using the Rapid Visco Analyser (RVA) - Visser, Magdalena Johanna (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc Food Sc)--University of Stellenbosch, 2011.